Do It Right, Do It Now! : People - the Essential Ingredient for Success. - Dembitz, John A. (London : Conrad Press, The, 2021)
A book for all. A book for existing and future leaders. A book for all those involved in managing people, in any capacity. John Dembitz has set down all the key ingredients for effective management and leadership in one easily readable book. As he emphasizes, there is no magic formula, just a willingness to engage, to be aware of others, to listen and to act. All his actions require is an attitude of mind, not capital investment. This is the only book you will ever need to read to become a better leader and manager and the results will be rapid! Do it Right; Do it Now!_x000D_'There are many books on management, some are highly theoretical. This is a very practical guide for business leaders, written by a successful entrepreneur and an extremely experienced, and current, Chair/Non-Executive Director. Definitely worth a read.'_x000D_Martin Scicluna Chair, J Sainsbury's plc and RSA Insurance plc._x000D__x000D_'If you haven't been there, seen it, done it and got the T-shirt you should read this book by the man who has. Packed with practical advice and distilled wisdom. No matter where you are on your organisational career from working on your own, to ultimately leading a global enterprise, there is plenty to learn and reflect on. Read it now and keep it by your side.' John M Neill, Chairman and Group Chief Executive Unipart group_x000D__x000D_'This isn't an academic, theoretical view of business. It's candid, hands-on, and personal. John has been there and done it right and shows you how you can too.'_x000D_Belden Menkus, Founder, Menkus & Associates.
BORED BOARD -- BUILDING LOYALTY/EXCEEDING EXPECTATIONS -- RESPECT -- COMMON SENSE -- CREATING AN OPEN AND RISK-FREE CULTURE -- ALIGNING ASPIRATIONS WITH REALITY -- PURSUIT OF THE BEST, 'NO' TO MEDIOCRITY -- TRAINING -- AGEISM AND OTHER 'ISMS'! -- REVIEW/FEEDBACK -- PROMOTING EARLY TO CREATE STRETCH -- FIRING -- RETAINING REALITY -- INTERNAL COMMUNICATION -- TRUST -- AUTHOR'S BACKGROUND… IN GREATER DETAIL -- SUMMARY OF DO IT RIGHT: DO IT NOW! CHAPTER BY CHAPTER.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Industrial management; Leadership; Electronic books